2011
DOI: 10.1021/jp201374h
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticle/Polymer Interfaces: All Atom Structures from Molecular Dynamics Simulations

Abstract: Molecular dynamics simulations have been performed to obtain detailed all-atom models of the interface between polystyrene (PS) and gold nanoparticles. Considering their relevance in the memory technology, systems containing gold nanoparticle included in PS polymer melts also in the presence of 8-hydroxyquinoline (8-HQ) molecules have been studied. Four different systems, including a coated or a noncoated nanoparticle, have been compared. Calculated radial density profiles show that the presence of noncoated n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 47 publications
3
57
0
Order By: Relevance
“…This feature of the Au−S interface, which exists also for self-assembled monolayers on bulk Au, has not been incorporated previously for AuNP simulations with classical force fields. 28,29,31,41 with the water density at the given temperature. The overall number of atoms in the simulated systems was around 33 000.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…This feature of the Au−S interface, which exists also for self-assembled monolayers on bulk Au, has not been incorporated previously for AuNP simulations with classical force fields. 28,29,31,41 with the water density at the given temperature. The overall number of atoms in the simulated systems was around 33 000.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…[41][42] More recently, reverse mapping procedures have also been applied to polystyrene 44,68 and to study gold nanoparticles polymer interfaces. 68 The extension of reverse mapping to nonequilibrium situations, such as the determination of the rheology, has been recently demonstrated for atactic polystyrene under steady shear flow. 69 In the following the proposed strategy for the reverse mapping of TX-100 is explained in detail.…”
Section: Reverse Mappingmentioning
confidence: 99%
“…4 A molecular dynamics study of gold nanoparticles interacting with a polystyrene interface showed that the presence of surfactant-stabilizer can cause significant disordering of the polystyrene chains compared to an uncoated particle, with performance implications for memorystorage devices. 5 It is therefore important to be able to control the shape and core accessibility of a nanoparticle via suitable choice of surfactant stabilizer and solvent conditions. 6,7 For example, Wieneke et al…”
Section: Introductionmentioning
confidence: 99%